Behavioral sleep medicine—The need for harmonization of clinical best practice outcome measures in children and adolescents with intellectual or developmental disabilities and restless sleep - Silvestri, Rosalia; Ipsiroglu, Osman S. (Frontiers in Psychiatry, 2022)
In behavioral medicine, sleep disorders, insomnia in particular, may be considered comorbidities and precipitating factors to intellectual or developmental disabilities (IDD). Nevertheless, sleep alterations have often been neglected in favor of daytime features and symptoms, albeit simple behavioral nighttime observations may disclose hypermotor features that characterize restless sleep. The root of most hypermotor restlessness is linked to central iron deficiency. The latter is often exacerbated by vitamin D deficiency (VDD), which interferes with both dopaminergic and serotonergic mechanisms. In this way, an imbalance affecting daytime behavior and mood is created. Several sleep-related motor disorders such as bruxism, periodic and aperiodic leg movements, Restless Legs Syndrome (RLS), and Restless Sleep Disorder (RSD) are commonly seen in Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorders (ASD). However, they are rarely diagnosed and often overlooked in affected children and adolescents. As a result, not only are these disorders not adequately addressed therapeutically, but their symptoms may be worsened by the side-effects of drugs used to contain disruptive daytime behavior, such as antipsychotics and antidepressants. In children with IDDs, obesity, inactivity and metabolic effects of antipsychotics often lead to Sleep Disordered Breathing (SDB), which is currently understood as an inflammatory state leading to “hyperactive” lethargy and further alterations of the hypoxic chain and vitamin D levels. Endorsing simple routine blood tests, including inflammatory markers such as C-reactive protein, ferritin, transferrin, and vitamin D levels, may favorably complement caregiver observations and ambulatory sleep recordings, leading to a sleep disorder diagnosis and consequent therapy. In fact, the treatment of SDB, RLS, and RSD has been copiously demonstrated to favorably impact vigilance, behavior, social competence, and academic skills in healthy and, to a greater extent, in IDD children. Thus, consulting and deliberating the root causes of functional and categorical diagnoses within a clinical framework may engender a more precise diagnosis and further benefit pediatric daytime and nighttime management of hyperactive behaviors.